Antibiotic Resistance of E. Coli Isolates from Broiler Chick's Cecum in Makassar City - Erdi Purwanto; Dini Marmansari; Dwi Kesuma Sari; Muhammad Hatta (Hasanuddin University, 2019)
Broiler chickens or broilers are the cheapest source of animal protein that can be obtained apart from eggs. The high demand for broiler chicken meat is fulfilled because modern broilers grow rapidly and are maintained massively and intensively. Massive maintenance systems make the spread of disease easier. Treatment of bacterial diseases using inappropriate antibiotics can lead to antibiotic resistance. This study aims to look at the antibiotic resistance of Escherichia coli (E. coli) bacteria from broiler chickens. E coli bacteria were isolated from 34 samples of broiler chicken cecum taken from several large traders in the city of Makassar. The E. coli isolates were then tested using Kirby-Bauer's diffuse disc method on 5 types of antibiotics from 5 classes of antibiotics namely: Ampicillin (β-lactam); Tetracycline (Tetracycline); Gentamicin (Aminoglycosides); Enrofloxacin (Flouroquinolone); Sulfamethoxazole-Trimethroprim (Sulfonamide). The inhibition zone formed was interpreted using the CLSI 2018 standard. The results of this study were 79.4% of the samples resistant to Ampisillin, 85.3% resistant to Tetracycline, 61.8% resistant to Sulfamethoxazole-Trimethroprim, 76.5% resistant to Enrofloxacin and 52.9% were resistant to Gentamicin. With 91.18% of the sample being resistant to at least 2 types of antibiotics.